Ethics and deontology teaching to doctors-interns at the department of pathological anatomy. - O. Dyadyk; V. Sil’chenko; I. Irkin; C. Shatrova; S. Rudenko; V. Zaritskaya (Морфологія, 2016)
The doctors – interns – pathologists while studying at the Department of Pathological Anatomy acquire necessary skills for independent work, as well as exploring issues of ethics and deontology, which are necessary in practice. The young physician-pathologist should follow the ethical principles in relations with physicians and relatives of the dead. If possible, should take into account their national and religious peculiarities. Knowledge of the deontological and ethical questions helps doctor-pathologist to observe the moral-ethical principles at the connection with clinicians and dead patient’s relatives.